2017
DOI: 10.15416/ijcp.2017.6.3.190
|View full text |Cite
|
Sign up to set email alerts
|

Illness Perceptions and Quality of Life in Patients with Diabetes Mellitus Type 2

Abstract: One of the treatment objectives in patients with type 2 diabetes mellitus (T2DM) is improving their quality of life (QoL). Illness perceptions are major determinant of QOL. This study was aimed to evaluate the QoL of T2DM patients with complications, and to examine the correlation between patients' illness perceptions and QoL. We conducted a cross-sectional study in a private hospital in Yogyakarta, Indonesia from July to September 2015. We recruited adult patients with a diagnosis of T2DM with complications (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Patients with mTBI who felt that medical interventions or medications could not manage their injury tended to have lower HRQOL one month later. This is also supported by previous diabetes mellitus research conducted in Indonesia and France on lung cancer, which reported that patients perceived treatment control to be related to HRQOL (Masson et al, 2020) (Perwitasari et al, 2017). Given that injury symptoms encountered after mTBI are significant for postinjury quality of life, nurses may consider providing case management that covers symptom management approaches such as pre-discharge discussions to ease the symptom burden on patients in the early recovery phase (Hung et al, 2023).…”
Section: Discussionmentioning
confidence: 63%
“…Patients with mTBI who felt that medical interventions or medications could not manage their injury tended to have lower HRQOL one month later. This is also supported by previous diabetes mellitus research conducted in Indonesia and France on lung cancer, which reported that patients perceived treatment control to be related to HRQOL (Masson et al, 2020) (Perwitasari et al, 2017). Given that injury symptoms encountered after mTBI are significant for postinjury quality of life, nurses may consider providing case management that covers symptom management approaches such as pre-discharge discussions to ease the symptom burden on patients in the early recovery phase (Hung et al, 2023).…”
Section: Discussionmentioning
confidence: 63%
“…An important point that we emphasize, although we discussed using the WhatsApp platform, improvements in attitudes, knowledge and perceptions can occur. We recommend the three components mentioned in the future related to problems of quality of life, and toughness in using the product in the long term, as part of the research we have applied before [5], [20], [21].…”
Section: Discussionmentioning
confidence: 99%
“…Research in Singapore and Indonesia shows that both hypoglycemia and hyperglycemia conditions are associated with a decrease in the QOL of DM patients [31,32]. Factors that play a role in failure of blood glucose control such as patients' medication adherence need to be considered in the care of DM patients in the primary health center (PHC) [33].…”
Section: Research Articlementioning
confidence: 99%